Respuesta :
7x² + 3x = 0
x(7x + 3) = 0 ⇔ x = 0 or 7x + 3 = 0 |subtract 3 from both sides
x = 0 or 7x = -3 |divide both sides by 7
x = 0 or x = - 3/7
Answer: B. {0; -3/7}
x(7x + 3) = 0 ⇔ x = 0 or 7x + 3 = 0 |subtract 3 from both sides
x = 0 or 7x = -3 |divide both sides by 7
x = 0 or x = - 3/7
Answer: B. {0; -3/7}
to solve the solution set of the problem, we can factor the expression given into x* ( 7x + 3 ) = 0. This dissects the equation into two parts:
x = 0
and
7x + 3 = 0x = -3/7
Hence the answer to this problem must be B. {0, -3/7}
x = 0
and
7x + 3 = 0x = -3/7
Hence the answer to this problem must be B. {0, -3/7}